Proposed Strategy and Implementation for Grand Atyasa Convention Center - Fabianto, M. Rizqi; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2014)
Abstract. Trend of beauty industry is growing rapidly in Indonesia. Now, the number of beauty clinics business have reached hundred of thousands. Other interesting fact that should be known about beauty clinic business is the majority of their customers are women. Carissa Beauty Clinic, as a new player in the industry of beauty clinic, saw a business opportunity to serve the women that are concerned about their skin and body health.The purpose of this final project is to provide suitable strategies for Carissa Beauty Clinic in corporate, business and functional level of the company in order to achieve their goals grew their business and maintain its existence. In addition to the increasing competition in the beauty clinic business, it indirectly requires any beauty clinics to have strategy that appeals to customers and provide the best service to satisfy customers. Methodology in this final project is by evaluating the external and internal environment in order to get the company’s strength, weakness, opportunity, and threat or SWOT. From the SWOT, corporate strategy can be created using TOWS matrix. The building of the TOWS matrix is supported by IFAS and EFAS table. After conducting analysis of both internal and external to the company, still many obstacles or barriers facing company such as competition is high in the beauty clinic business, replacement products that sold freely on the market, human resource are still weak, incomplete clinical infrastructure, marketing strategies are not effective, and lack of ability of the company to establish a relationship with customers.Strategy recommendation as a solution to Carissa Beauty Clinic is to improve the internal barriers faced by the company such as improve service to customers and maintain the quality of service, creating products and latest innovative treatment program, strengthening the organizational structure of the company, information technology applications for operational activities, using the media for promotional activities and information for costumers, and start making CSR (Corporate Social Responsibility) as establishment of brand image in the community. This strategy should be monitored and assessed as very influential for the condition of the company in the future. For that measurement strategies should be conducted to determine whether the strategy can meet the company's objectives so as to maintain a presence and is able to grow any further.Keywords: competition, beauty clinic business, growth strategy